2011
DOI: 10.1051/0004-6361/201117505
|View full text |Cite
|
Sign up to set email alerts
|

The energetics of giant radio galaxy lobes from inverse Compton scattering observations

Abstract: Context. Giant radio galaxy (GRG) lobes are excellent laboratories for studying the evolution of the particle and magnetic field energetics and the past activity of radiogalaxy jets, as indicated by recent results of X-ray observations with Suzaku. However, these results are based on assumptions of the shape and extension of the GRG lobe electron spectrum. Aims. We re-examine the energetics of GRG lobes as derived by inverse Compton scattering of cosmic microwave background (CMB) photons (ICS-CMB) by relativis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…∼ E −αr ), which is expected to have the same value of α X (see, e.g., Longair 2003). Observations of the ICCMB spectrum at high energies (X-rays or gamma-rays) can also set the absolute normalization (assuming a unique spectral slope α) of the electron spectrum used for the SZE calculations (see Colafrancesco & Marchegiani 2011). Given the shape of the electron spectrum, the total intensity and the spectral shape of the SZE in RG lobes depend on the minimum en-ergy of the electron distribution (see, e.g., Colafrancesco 2008, Colafrancesco & Marchegiani 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…∼ E −αr ), which is expected to have the same value of α X (see, e.g., Longair 2003). Observations of the ICCMB spectrum at high energies (X-rays or gamma-rays) can also set the absolute normalization (assuming a unique spectral slope α) of the electron spectrum used for the SZE calculations (see Colafrancesco & Marchegiani 2011). Given the shape of the electron spectrum, the total intensity and the spectral shape of the SZE in RG lobes depend on the minimum en-ergy of the electron distribution (see, e.g., Colafrancesco 2008, Colafrancesco & Marchegiani 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Observations of the ICCMB spectrum at high energies (X-rays or gamma-rays) can also set the absolute normalization (assuming a unique spectral slope α) of the electron spectrum used for the SZE calculations (see Colafrancesco & Marchegiani 2011). Given the shape of the electron spectrum, the total intensity and the spectral shape of the SZE in RG lobes depend on the minimum en-ergy of the electron distribution (see, e.g., Colafrancesco 2008, Colafrancesco & Marchegiani 2011. In this context, it has been shown that the ICCMB X-ray emission provides only marginal constraints to the minimum energy of the electron population in the lobes (Colafrancesco 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Erler et al 2015), and possible detection of the nonthermal SZE can give information on the properties of the electrons which are not depending on the magnetic field properties (see e.g. Colafrancesco & Marchegiani 2011 for the case of radio galaxies lobes). In the hard X-ray and gamma rays, the possible detection of the Inverse Compton emission from relativistic electrons in relics can constrain their high-energy spectra, allowing to discriminate between the acceleration and adiabatic compression scenario (see Paulo, Colafrancesco & Marchegiani 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For an average GRG in the microwave range, the area around which is built by stacking, it was found that 1) there is a positive signal in the millimeter range; 2) the spectrum in the millimeter range is flat; 3) the signal in the submillimeter range is absent; 4) the topological properties in the average CMB fluctuations map possess special features: a weak insignificant maximum (< 1σ) is located in the minimum zone; 5) a significant SZ-effect, related with the scattering of CMB photons by the electrons of the GRG jet plasma [18] is not observed. A comparison with other populations of objects has revealed that given the average microwave properties, the distant radio galaxies with redshift ranges 0.3 ≤ z < 0.7.…”
Section: Discussionmentioning
confidence: 99%